Herramienta visual para exploración de datos en una cohorte de niños canguro durante su primer año de vida (2017)
The Fundación Canguro has been providing care for newborn premature infants in Colombia since 1994, helping them overcome the many issues related to their birth conditions. As part of their mission they have collected a longitudinal database of more than 33,000 children, recording their evolution during 23 years, with 47 measured variables. Having such rich data is both a blessing and a curse, as deriving insights from it is a daunting task. In this paper we present the results of a visual analytics project that has been enabling the analysts of the Fundación Canguro to derive insights in ways they couldn?t do before. To support the project, we present a process model that can be applied to any time based process where the results of an event are evaluated. For the problem at hand, the model considers the environment (before the event), pregnancy (development of the event), birth (the event), and growth (after the event). Using this model, a visual analytics tool was developed and implemented, and has been used by the analysts for the last months for deriving insights...